Study on the Modification in Physical and Optical Properties of Lithium Bismuth Borate Glasses with Vanadium Oxide Addition - V. D. Raut; A. V. Deshpande; N. S. Satpute (Research Trends and Challenges in Physical Science Vol. 5, 2021)
The series of the glasses with general formula (40-x)Li2O:30B2O3:30Bi2O3:xV2O5, with x = 0, 0.5, 1.0, 1.5 and 2.0 mol% was prepared using conventional quenching technique. The glass transition temperature Tg for these samples were determined from Differential Thermal Analysis. The glass transition temperature increases beyond 0.5 mol%. It was found that the glasses under study consist of randomly connected BO3 & BO4 structural units. The density and molar volume of glasses were found to depend on V2O5 content. Initially the density increases, molar volume and glass transition temperature decrease with the addition of V2O5. This suggests that when V2O5 is added to the glass initially up to 0.5 mol% it may be entering as a modifier. Beyond 0.5 mol% density decreases and molar volume increases as V2O5 goes as former. This reveals the role of V2O5 as a glass network former beyond 0.5 mol%. Optical band gap energy decreases and cut off wavelength increases with increase in V2O5 content. Author wish to study the effect of transition metals on the optical properties of the lithium bismuth borate glasses